2017
DOI: 10.1017/s0033291717002264
|View full text |Cite
|
Sign up to set email alerts
|

The nature and efficacy of culturally-adapted psychosocial interventions for schizophrenia: a systematic review and meta-analysis

Abstract: The adaptation process can be described within a framework that serves as a benchmark for development or assessment of future adaptations. Culturally adapted interventions were more efficacious than usual treatment in proportion to the degree of adaptation. There is insufficient evidence to show that adapted interventions are better than non-adapted interventions. Features of context, intervention and design influenced efficacy. Investigating whether adaptation improves efficacy, most importantly amongst ethni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(111 citation statements)
references
References 86 publications
(259 reference statements)
5
106
0
Order By: Relevance
“…The cultural adaptation process of family interventions in the Arab world was consistent with some of the themes found in previous studies including language, content, concepts and illness models, cultural norms and practice, context and delivery (11,13,14). The language of the original manuals was translated into Arabic and the content was modified to fit the cultural and religious norms and values.…”
Section: Discussion 12supporting
confidence: 71%
See 1 more Smart Citation
“…The cultural adaptation process of family interventions in the Arab world was consistent with some of the themes found in previous studies including language, content, concepts and illness models, cultural norms and practice, context and delivery (11,13,14). The language of the original manuals was translated into Arabic and the content was modified to fit the cultural and religious norms and values.…”
Section: Discussion 12supporting
confidence: 71%
“…Recently, researchers have shown an increased interest in culturally adapting family interventions to different cultures to improve the acceptability and effectiveness of the treatment (7,(13)(14)(15)(16)(17)(18). These studies have shown that there is optimal benefit when interventions are tailored for a specific culture.…”
Section: Introductionmentioning
confidence: 99%
“…However, just as adaptations have the potential to improve the impact and durability of treatment, it is also plausible that adaptations may compromise the delivery of essential treatment mechanisms (Drake et al, 2001). Cultural adaptations research provides one such example of this tension; meta‐analyses reflect mixed evidence on the necessity and impact of cultural adaptations, with some citing adaptations as beneficial for clinical outcomes and implementation efforts (e.g., Benish, Quintana, & Wampold, 2011; Degnan et al, 2018; Hall, Ibaraki, Huang, Marti, & Stice, 2016; Van Mourik, Crone, De Wolff, & Reis, 2017), and others finding no added utility in modifying protocols (e.g., Huey & Polo, 2008; Huey & Polo, 2017; Thomas, Abell, Webb, Avdagic, & Zimmer‐Gembeck, 2017). Overall, there is continued debate on whether fidelity to manualized therapies should be prioritized over flexibility and local adaptations to the intervention for particular clients or contexts (Hamilton, Kendall, Gosch, Furr, & Sood, 2008; Owen & Hilsenroth, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ethnic differences might have a great impact on received diagnoses [8]. Considering culture and adapting intervention accordingly improves response [9].…”
Section: Editorialmentioning
confidence: 99%